2022
DOI: 10.1093/ofid/ofac640
|View full text |Cite
|
Sign up to set email alerts
|

An Elastic Net Regression Model for Identifying Long COVID Patients Using Health Administrative Data: A Population-Based Study

Abstract: Background Long COVID patients experience persistent symptoms after acute SARS-CoV-2 infection. Healthcare utilization data could provide critical information on the disease burden of long COVID for service planning, however, not all patients are diagnosed or assigned long COVID diagnostic codes. We developed an algorithm to identify individuals with long COVID using population-level health administrative data from British Columbia (BC), Canada. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Prior research found low concordance between the ICD-10 code for PCC and the clinical criteria for the disease, (4) and a right-skewed distribution of PCC diagnoses across clinicians. (5) Prior machine learning-based studies that focused on counterfactual probability of diagnosis had patients visited specialty PCC clinics all found different estimates of the mean risk of PCC following COVID-19, ranging from approximately 20% in Binka, et al to over 40% in Pfaff, et al(7,8) This mirrors an even wider difference in estimates derived from prospective patient surveys, which range from 4.5% to 89% --a difference that has been attributed to heterogeneous case definitions. (27) Our study’s results also agreed with prior research that found PCC diagnoses demographically cluster among non-Hispanic white female patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research found low concordance between the ICD-10 code for PCC and the clinical criteria for the disease, (4) and a right-skewed distribution of PCC diagnoses across clinicians. (5) Prior machine learning-based studies that focused on counterfactual probability of diagnosis had patients visited specialty PCC clinics all found different estimates of the mean risk of PCC following COVID-19, ranging from approximately 20% in Binka, et al to over 40% in Pfaff, et al(7,8) This mirrors an even wider difference in estimates derived from prospective patient surveys, which range from 4.5% to 89% --a difference that has been attributed to heterogeneous case definitions. (27) Our study’s results also agreed with prior research that found PCC diagnoses demographically cluster among non-Hispanic white female patients.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Binka, et al used ridge regression with administrative data from British Columbia for the same aim. (8) Among the high-prevalence test set of patients attending or diagnosed at a specialty PCC clinic, all achieved good performance, though the generalizability to patients outside that setting is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Initial work focused on the use of machine learning approaches to identify long-COVID patients in administrative datasets. In our first paper, an elastic net regression model leveraging several BCC19C datasets was used to create an algorithm for identifying long-COVID patients ( 23 ). Clinical data on individuals enrolled in post-COVID-recovery clinics in BC were integrated into the BCC19C to develop and validate the algorithm.…”
Section: Findings To Datementioning
confidence: 99%
“…Binka et al ( 2022 ) detect Long COVID cases from health administrative data, including demographic features, pre-existing conditions, COVID-19-related data and all symptoms recorded 28 days after the COVID-19 symptom index date and lasted up to 183 days afterwards.…”
Section: Literature Reviewmentioning
confidence: 99%